MEMINIMALKAN KECECACATAN HAK SEPATU PADA PROSES PRODUKSI GUNA MENINGKATKAN KUALITAS PRODUK di PT. ANGKADA RAYA - Mukhammad Misbakh Saffana; Siti Mundari (LPPM Universitas Bina Bangsa, 2023)
PT Angkada Raya is engaged in the shoe heel manufacturing industry, experiencing a decline in production due to defective products. By using the seven tools, product quality is analyzed, and factors that cause defects are identified. The company has a low level of quality control, with a defect percentage of 3.63%. Factors such as workers, work methods, environment, and machines contribute to these defects. To minimize the number of defects, standardization is carried out, improving production methods, improving the work environment. After this implementation, the percentage of defects decreased to 1.96%. PT Angkada Raya is committed to continuously improving product quality through effective quality control